Staging depth : Eugene O'Neill and the politics of psychological discourse - Pfister, Joel. (Chapel Hill : University of North Carolina Press, 1995)
Pfister examines the history of the middle-class family and of Freudian pop psychology in the 1910's and 1920's to reconstruct the cultural conditions for the imagining and popularizing of "depth", a trope that was central to O'Neill's dramatic vision
Foreword / Alan Trachtenber -- Introduction: the profession of "Depth" -- Beyond biography -- O'Neill and the making of the psychological family -- The psychological dyad in the "Land of the mother complex" the historicity of ambivalence -- "Depth" as a mass-cultural category -- Pop psychology, the professional-managerial class, and the aesthetic of depth -- The therapeutic playwright and therapeutic theatre -- The production of "Psychological" common sense for the professional-managerial class -- The psychological as a political and historical category -- O'Neill's critique of psychological discourse and iceman -- The ideological work of "Depth" O'Neill and the American left -- Workers, race, and psychological primitives -- O'Neill and the anarchist-feminist critique of personal life -- The propaganda of "Life" O'Neill, the left, and social depth -- Ah wilderness! and the reproduction of the middle class -- Possessors, self-dispossessed -- The trappings of theatre, gender, and desire.
Includes bibliographical references (pages 289-313) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: O'Neill, Eugene, -- 1888-1953 -- Knowledge -- Psychology; O'Neill, Eugene, -- 1888-1953 -- Et la psychologie; O'Neill, Eugene, -- 1888-1953; O'Neill, Eugene, -- (1888-1953) -- Critique et interprétation.; O'Neill, Eugene, -- (1888-1953) -- Pensée politique et sociale; O'Neill, Eugene, -- (1888-1953) -- Psychologie; O'Neill, Eugene; O'Neill, Eugene, -- 1888-1953 -- Knowledge -- Psychology; Literature and society -- United States -- History -- 20th century; Domestic drama, American -- History and criticism; Drama -- Psychological aspects; Middle class in literature; Psychology in literature; Families in literature; Littérature et société -- États-Unis -- Histoire -- 20e siècle.; Théâtre bourgeois américain -- Histoire et critique; Classes moyennes dans la littérature.; Psychologie dans la littérature.; Familles dans la littérature.; Théâtre (Genre littéraire) -- Aspect psychologique; DRAMA -- American; Domestic drama, American; Drama -- Psychological aspects; Families in literature; Literature and society; Middle class in literature; Psychology; Psychology in literature; United States; Psychologie; Literatur; Cultuurverandering; Verenigde Staten; Historisch kritische methode; Literatuursociologie; Middenklassen; Literatuurpsychologie; Psychologie -- Dans la littérature.; Littérature et société -- États-Unis -- Histoire -- 20e siècle.; Classes moyennes -- Dans la littérature.; Famille -- Dans la littérature.; Literature and society -- United States -- 20th century; Domestic drama, American -- History and criticism; Middle class in literature; Psychology in literature; Families in literature; 1900-1999; Electronic books; Criticism, interpretation, etc; History